Αlpha-thalassemia genotypes in Vietnam: a report of 12,030 pregnant women and their husbands performing prenatal screening for alpha-thalassemia (Faculty of Medicine Universitas Indonesia, 2023)
BACKGROUND Αlpha (α)-thalassemia is a global health concern, and improving screening methods is crucial for disease prevention. This study aimed to assess α-thalassemia genotypes and evaluate the effectiveness of various thresholds for mean corpuscular volume (MCV) and mean corpuscular hemoglobin (MCH) in prenatal screening for α-thalassemia. METHODS This cross-sectional study included pregnant women and their husbands who underwent prenatal screening for thalassemia at the National Hospital of Obstetrics and Gynecology, Vietnam from January 2012 to August 2021. Blood samples were collected and analyzed using the strip assay technique, which can detect 21 common mutations in the α-globin gene and 22 common mutations in the beta-globin gene. RESULTS Of the 12,030 participants, 931 were identified as having α-thalassemia, with –SEA, -α3.7, and -α4.2 being the most common mutations. When examining different thresholds of MCV and MCH, MCV <85 fL and MCH <28 pg had a lower missing rate than MCV <80 fL and MCH <27 pg, respectively. MCH <28 pg showed the highest sensitivity in screening for α-thalassemia. MCV <85 fL showed the lowest positive predictive value (PPV). The combination of MCV <80 fL and MCH <27 pg showed the lowest sensitivity in screening for α-thalassemia but the highest PPV among all thresholds. CONCLUSIONS Optimizing the screening methods for α-thalassemia is important for preventing and managing the disease in the community. These findings have important implications for thalassemia prevention and management programs and may contribute to reducing the burden of thalassemia in the global population.